New method and algorithm of three-dimensional turbine guide blade rim optimization - Boiko, Anatoli; Govorushchenko, Yuri; Burlaka, Maksym (ASME, 2010)
The new method and algorithm of three-dimensional turbine guide blade rim optimization were proposed using CFD-calculations, guide blade deformation and reasonable computation time consuming optimization approach. Verification of three-dimensional CFD-calculations results are presented by comparison with experimental data. The reasonableness of the isolated guide blade rim optimization of a turbine stage is justified. Two methods of the complex tangential lean implementation are compared. The parametric model is developed allowing conservation of the mass flow rate through the blade passage during optimization process. Both a bowing method and computational grids construction are realized in specialized program TOpGrid. The gained grids has been written in formatCGNS(CFDGeneral Notation System). The optimization approach is grounded on a combination of the DOE theory and Monte-Carlo method. The algorithm of optimization of guide blade rim is described. The examination of aerodynamic optimization efficiency with the developed algorithm of a guide blade rim at different a/l (a-throat of the channel, l-height of a blade) was carried out. The analysis of the results of the computation and physical explanation of reasons of a turbine blade passage efficiency rise is given.
Keywords: turbine; optimal design; 3D-optimization; guide blade rim; CFD; guide blade deformation; tangential lean; computational grid; Monte-Carlo method; DOE; efficiency of turbine; турбіни; оптимальне проектування; 3D-оптимізація; напрямний апарат; деформація напрямної лопатки; тангенціальний нахил; розрахункова сітка; метод Монте-Карло; планування експерименту (DOE); ефективність турбіни